2002
DOI: 10.1095/biolreprod66.5.1336
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxycholesterol Is Produced by Testicular Macrophages During the Early Postnatal Period and Influences Differentiation of Leydig Cells In Vitro1

Abstract: Leydig cells develop inappropriately in animals lacking testicular macrophages. We have recently found that macrophages from adult animals produce 25-hydroxycholesterol, an oxysterol involved in the differentiation of hepatocytes and keratinocytes. Therefore, we hypothesized that testicular macrophages also produce 25-hydroxycholesterol during the early postnatal period and that this oxysterol plays a role in the differentiation of Leydig cells. We assessed the production of 25-hydroxycholesterol and 25-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…It remains possible, nevertheless, that changes in ALC differentiation may have been affected by altered macrophage numbers. Previous studies have suggested that macrophages generally enhance LC function and development (Chen et al, 2002;Gaytan et al, 1994), although activation of macrophage invasion can have an inhibitory effect (Hales, 2002). In this case, it appears unlikely that the marked reduction in ALC development following SC ablation is caused by the transient increase in macrophage numbers for the following three reasons.…”
Section: Discussionmentioning
confidence: 80%
“…It remains possible, nevertheless, that changes in ALC differentiation may have been affected by altered macrophage numbers. Previous studies have suggested that macrophages generally enhance LC function and development (Chen et al, 2002;Gaytan et al, 1994), although activation of macrophage invasion can have an inhibitory effect (Hales, 2002). In this case, it appears unlikely that the marked reduction in ALC development following SC ablation is caused by the transient increase in macrophage numbers for the following three reasons.…”
Section: Discussionmentioning
confidence: 80%
“…Like TNF-α, interleukin-1 inhibits testosterone secretion (Hutson, 1994;Hales, 1996) and, for the same reasons as mentioned above for TNF, is also not likely to mediate the effects of bismuth on testosterone secretion given the present findings that bismuth kills macrophages. Testicular macrophages also make 25-hydroxycholesterol, an oxysterol that is known not only to be converted to testosterone by Leydig cells but also to stimulate steroidogenic acute regulatory protein (StAR) production (Nes et al, 2000;Lukyanenko et al, 2001;Chen et al, 2002;King et al, 2004). Therefore, its effects are entirely stimulatory on Leydig cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin 1 and other factors secreted by macrophages could reach the Leydig cells via diffusion of small light vesicles that were extruded from the macrophages as reported here. Recent studies have revealed the effect of 25-hydroxycholesterol secreted by testicular macrophages on Leydig cells as well as the regulation of 25-hydroxycholesterol production in testicular macrophages by testosterone (Nes et al 2000;Lukyanenko et al 2001Lukyanenko et al , 2002Chen et al 2002).…”
Section: Leydig Cell-macrophage Interactionsmentioning
confidence: 99%
“…The selective depletion of macrophages prevents Leydig cell repopulation in ethylene dimethane sulfonate (EDS)-treated rats, as well as the response of Leydig cells to gonadotropin treatment (Gaytan et al 1995b). Testosterone production by Leydig cells and the secretion of 25-hydroxycholesterol by testicular macrophages have been shown to be interdependent (Lukyanenko et al 2001Chen et al 2002). The vascular endothelial growth factor (VEGF) influences the differentiation and function of endothelial cells as well as of Leydig cells (Setchell and Palombi 2004;Anand et al 2003).…”
Section: Introductionmentioning
confidence: 99%